A Comparison of Social Support among Adolescents with and without Visual Impairments in Jordan: A Case Study from the Arab Region. (September 2014) - Hadidi, Muna S.; Khateeb, Jamal M. Al
Introduction: Research to date on social support for adolescents with visual impairments (that is, blindness or low vision) has been primarily carried out in developed countries, and very little is known about the social support systems that are available for such adolescents in developing countries such as those in the Arab world. In the present study, social support among adolescents with and without visual impairments was investigated in Jordan, which is considered a developing country. Methods: Study participants included 86 adolescents with visual impairments and 73 sighted adolescents. The instrument used to collect information in this study was an Arabic version of the Multidimensional Scale of Perceived Social Support (MSPSS). Results: The level of social support reported by adolescents with visual impairments was higher than that reported by sighted adolescents. In all three domains of the MSPSS (family, friends, and significant others), students with visual impairments reported receiving more social support than those without impairments. However, there was no statistically significant effect for gender. Discussion: The results of the study are not consistent with findings of previous studies, all of which were conducted in Western countries. The disparities in experiences of adolescents with visual impairments in developed and developing countries may be attributed to differences in cultural values as well as to the conceptualization of support by those involved. Implications for practitioners: Special education teachers need to be aware of the cultural backgrounds of their students and to develop and implement culturally appropriate programs for them.